2020
DOI: 10.1177/2633105520935104
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Early-Life Iron Deficiency on Brain Energy Metabolism

Abstract: Iron deficiency (ID) is one of the most prevalent nutritional deficiencies in the world. Iron deficiency in the late fetal and newborn period causes abnormal cognitive performance and emotional regulation, which can persist into adulthood despite iron repletion. Potential mechanisms contributing to these impairments include deficits in brain energy metabolism, neurotransmission, and myelination. Here, we comprehensively review the existing data that demonstrate diminished brain energetic capacity as a mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 248 publications
0
38
0
Order By: Relevance
“…Even though the need for iron to promote fetal and future infant development is well known ( 91 ), the effect of iron deficiency on fetal growth is somewhat controversial. An older meta-analysis on the effect of iron supplementation during pregnancy commissioned by the WHO found that iron supplementation increased birth weight by 100 g at most ( 92 ).…”
Section: Discussionmentioning
confidence: 99%
“…Even though the need for iron to promote fetal and future infant development is well known ( 91 ), the effect of iron deficiency on fetal growth is somewhat controversial. An older meta-analysis on the effect of iron supplementation during pregnancy commissioned by the WHO found that iron supplementation increased birth weight by 100 g at most ( 92 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the severity of adverse effects on brain development will depend primarily on how timely, dose and duration any nutrient deficiency exists, and will depend on the coincidence of two factors: the time of accelerated growth, development and development in a nutrient-dependent area and the probability of nutrient deficiency in this age. [30][31] Since it is an essential method, nutrients are required for optimal brain maturation, and brain development is especially susceptible to metabolic homeostasis disruption. 31 In the first year of development, the brain is undergoing an incredible transformation into a complex organ.…”
Section: The Importance Of Iron In Brain Developmentmentioning
confidence: 99%
“…Perinatal-life iron deficiency (ID) impairs energy metabolism in a brain region- and age-dependent manner, in particular in hippocampal neurons [ 84 ]. Iron-containing proteins involved in brain energy metabolism are aconitase (TCA), succinate dehydrogenase iron-sulfur, and cytochrome b subunits (complex II) (TCA, ETC), NADH dehydrogenase iron-sulfur proteins 1–8 (complex I) (ETC), ubiquinol:cytochrome c oxidoreductase (complex III) (ETC), cytochrome c (ETC), and cytochrome c oxidase (complex IV) (ETC) [ 84 ].…”
Section: Metabolite Supply For Liver Function and Energy Supply Fomentioning
confidence: 99%